VD_FINDINFO Décision / 2014 / 1017 vom 30. September 2014 - VD Tribunal cantonal (2014)
INDEMNITÉEN GÉNÉRAL, CLASSEMENT DE LA PROCÉDURE | 393 al. 1 let. a CPP (CH), 429 al. 1 let. a CPP (CH), 433 al. 1 CPP(CH)